Isolation of adult pituitary stem/progenitor cell clusters located in the parenchyma of the rat anterior lobe - Yoshida, Saishu; Nishimura, Naoto; Ueharu, Hiroki; Kanno, Naoko; Higuchi, Masashi; Horiguchi, Kotaro; Kato, Takako; Kato, Yukio (Stem cell research, 2016)
Recent studies have demonstrated that Sox2-expressing stem/progenitor cells play roles in the pituitary cell turnover. Two types of niches have been proposed for stem/progenitor cells, the marginal cell layer (MCL) and the dense cell clusters in the parenchyma. Among them, the appearance of the parenchymal-niche only after birth indicates that this niche is involved in the cell turnover required for the postnatal pituitary. However, little is known about the roles of the parenchymal-niche and its regulation. The present study aimed to isolate pituitary stem/progenitor cells from the parenchymal-niche in the adult rat pituitary. Cell dispersion by stepwise treatment with proteases allowed the isolation of dense cell clusters. Immunocytochemistry demonstrated that clusters are universally composed of SOX2-positive cells, and most of them are positive for PROP1. Taken together with the anatomical analysis, we concluded that the isolated clusters are the parenchymal stem/progenitor cell (PS)-clusters, not the MCL-one. PS-clusters cultivated by serum-free overlay 3-dimensional culture maintained their stemness, and treatment with bFGF and EGF induced cyst-formation. Moreover, PS-clusters demonstrated some differentiation capacity with GSK3β-inhibitor treatment. Collectively, the present study demonstrates a simple method for isolating stem/progenitor cells from the parenchymal-niche, and provides tools to analyze the factors for regulating the pituitary niches. •Isolation of the pituitary stem/progenitor cell niche forming dense cell cluster.•Dense cell clusters are classified into three subtypes referring to S100β.•Cultivation by the serum-free 3D culture maintains their undifferentiated state.•Inhibition of GSK3β induces PS-cluster to differentiate into hormone-producing cells.